Relationship between knee abduction moment with patellofemoral joint reaction force, stress and self-reported pain during stair descent in women with patellofemoral pain - Waiteman, Marina Cabral [UNESP]; Briani, Ronaldo Valdir [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; Ferreira, Amanda Schenatto [UNESP]; Ferrari, Deisi; Silva, Danilo de Oliveira [UNESP]; Azevedo, Fabio Micolis de [UNESP] (Elsevier B.V., 2018)
Background: Increased external knee abduction moment has been proposed as a risk factor for patellofemoral pain. This alteration is thought to be associated with elevated patellofemoral joint reaction force and stress, however these relationships remain poorly explored. Therefore, this study aimed at comparing knee abduction moment parameters (peak, rate of moment development and impulse), patellofemoral joint reaction force and stress of women with patellofemoral pain and pain-free controls during stair descent; and investigating the relationship among these variables with self-reported pain. Methods: Kinetic data was obtained by inverse-dynamics equations and a previously reported algorithmic model was used to determine patellofemoral joint reaction force and stress. Participants' worst pain in the last month and pain level during stair descent were evaluated using a visual analogue scale. Findings: Women with patellofemoral pain presented higher peak, rate of moment development and impulse of the external knee abduction moment, patellofemoral joint reaction force and stress (p = 0.005 to 0.04, effect size = 0.52 to 0.96) during stair descent than pain-free controls. Only knee abduction moment impulse presented positive moderate correlations with worst pain level in the last month (r = 0.53, p < 000.1), pain level during stair descent (r = 0.33, p = 0.042), patellofemoral joint reaction force (r = 0.65, p < 000.1) and stress (r = 0.58, p < 000.1). Interpretation: These findings indicate that strategies aimed at decreasing external knee abduction moment impulse could reduce the load over the patellofemoral joint and improve pain of women with patellofemoral pain.
Keywords: Knee abduction moment; Knee; Anterior knee pain; Kinetics; Biomechanics